Reindeer husbandry in peril?—How extractive industries exert multiple pressures on an Arctic pastoral ecosystem - Fohringer, Christian; Rosqvist, Gunhild; Niila, Inga; Singh, Navinder (2021)
Environmental changes and their consequences on biodiversity are known to have far-reaching effects on the resilience of animal populations and associated livelihoods around the world. To counteract negative demographic and economic effects on pastoralism, knowledge about the historical and current status of the environment is essential. In this study, we show how extractive industries, especially large-scale mining, induced a cascade of land conversions which are affecting animal populations and pastoralists’ adaptive responses in northern Sweden. We examine social–ecological vulnerability in Arctic reindeer husbandry by integrating herders’ knowledge, population statistics for semi-domesticated reindeer Rangifer t. tarandus, public data on socio-economic variables and geospatial tools. We determine that approximately 34% of Laevas reindeer herding community's grazing grounds are functionally unavailable to reindeer at present due to the accumulation of multiple competing land use pressures. Reindeer numbers currently only remain stable due to increased management efforts. Moreover, we identified current hotspots of high cumulative impact and mineral exploration as the spatially dominating land use factor in this area. Our approach and results provide new insights for scientifically robust cumulative impact assessments of anthropogenic stressors by creating a baseline of current developments via a combination of reindeer herder's knowledge with historical data of trends and extents of human activity over the last century.